MAKNA DENOTATIF DAN KONOTATIF ANTOLOGI PUISI KOPI KEHIDUPAN KARYA MR. SAE - Ambar Cahyastri; Een Nurhasanah; Wienike Dinar Pratiwi (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the denotative meaning and connotative meaning in fourteen poetry titles in the poetry anthology Kopi Kehidupan by Mr. Sae. This research uses qualitative research type with a qualitative descriptive method. The data used are words, phrases, clauses, or sentences contained in the poetry anthology Kopi Kehidupan by Mr. Sae. The data collection technique is in the form of document analysis and poetry literary works with listening and recording techniques. The data analysis technique in this research has three stages, namely data reduction, presenting data, and verification/conclusion drawing. The results of the analysis of denotative and connotative meanings in the poetry anthology Kopi Kehidupan by Mr. Sae found 16 denotative meanings and 18 connotative meanings. This shows that the poet is more dominant in using connotative meaning than denotative meaning.